A4NH 2019 annual report - CGIAR Research Program on Agriculture for Nutrition and Health (International Food Policy Research Institute, 2020)
Food systems are changing rapidly in low- and middle-income countries. These countries seek food-based solutions for better nutrition and health of all people while addressing challenges of sustainability, inequity, and malnutrition. The CGIAR Research Program on Agriculture for Nutrition and Health (A4NH) works to develop evidence to support policies and actions for healthier food systems. A4NH is a consortium of seven managing partners, led by the International Food Policy Research Institute (IFPRI). This report summarizes 2019 research results from A4NH, across five research flagships, and highlights the partnerships through which research has led to outcomes in five focus and more than two dozen other partner countries.